Latitudinal features of Total Electron Content over the African and European longitude sector following the St. Patrick's day storm of 2015. Issue 7 (1st April 2018) - Paul, A.; Kascheyev, A.; Rodriguez-Bouza, M.; Pathak, K.; Ferreira, A.A.; Shetti, D.; Yao, J.N.
Abstract: GNSS TEC values have been obtained from 18 stations distributed from the magnetic equator to nearly 80°N magnetic dip in the African and west-European longitude sector corresponding to the March 17–18, 2015 geomagnetic storm. Significantly depleted ionosphere have been observed at stations north of 50°N geographic on March 18, 2015 following the above storm over a longitude swath 11.9°–21°E covering the Eastern Africa and Western European longitude sector. High ROTI values were noted on March 17 th at locations around 80°N magnetic dip. Two prominent peaks in PCN were noted around 09:00 UT and 14:00 UT on March 17, 2015 and around 15:00 UT on March 18, 2015. Daytime thermospheric (O/N2 ) ratio was markedly less on March 18th at latitudes above 60°N geographic which is suggested to be the major driver behind depleted high latitude ionosphere during the recovery phase of the storm on March 18, 2015.